The genus Buenoa Kirkaldy, 1904 (Hemiptera: Heteroptera: Nepomorpha: Notonectidae) in northern Brazil: inventory, new records, and new species - Barbosa, Julianna Freires; Nessimian, Jorge Luiz (Zootaxa, 2013)
The genus Buenoa contains 69 described species, 15 occurring in the North Region of Brazil. Here we present new records for the States of Pará, Amazonas, Roraima, and Rondônia. We examined 16 species: B. amnigenoidea Nieser, 1970, B. amnigenopsis Nieser, 1975, B. amnigenus White, 1879, B. exilidens Barbosa, Nessimian & Ferreira-Keppler, 2010, B. dilaticrus Barbosa, Nessimian & Ferreira-Keppler, 2010, B. femoralis (Fieber, 1851), B. fuscipennis (Berg, 1879), B. incompta Truxal, 1953, B. konta Nieser & Pelli, 1994, B. macrotrichia Truxal, 1953, B. platycnemis (Fieber, 1851), B. salutis Kirkaldy, 1904, B. tarsalis, Truxal, 1953, B. tibialis Truxal, 1957, B. truxali Nieser, 1968, and B. unguis Truxal, 1953; and a new species, B. deplanatylus Barbosa & Nessimian sp. nov. We found no material of four species with bibliographic records for the region: B. communis Truxal, 1953, B. pallens (Champion, 1901), B. pallipes (Fabricius, 1803), and B. paranensis Jaczewski, 1928.